Extração e caracterização qualitativa do óleo da polpa e amendoas de frutos de macaúba [Acrocomia aculeata (Jacq) Lodd. ex Mart] coletada na região de Botucatu - SP - Amaral, Fabiano Pereira do [UNESP] (2011)
The international energy situation indicates to the depletion of oil reserves in the short term. Brazil, considering its potential, has sought through public policy, encourage the study of alternative forms of energy. Many of these forms are based on sub-products and agricultural products, especially the ethanol industry for fuel purposes. Another alternative of vegetable origin, most recently discussed, would be the production of fuel oil called biodiesel. The study aimed to extract and measure the pulp oil production of macaúba palm [Acrocomia aculeata (Jacq) Lodd. ex Mart], collected in Botucatu (SP). In addition, the qualitative analysis of the pulp and almond oil are determined. The results showed low productivity in oils, compared to the reported for macauba natural populations of Minas Gerais. The qualitative analysis of the macauba pulp shows to be rich in long chain fatty acids, while the almond have significant amounts of lauric acid.